2020
DOI: 10.1172/jci.insight.136215
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic lipids promote liver metastasis

Abstract: Obesity predisposes to cancer and a virtual universality of nonalcoholic fatty liver disease (NAFLD). However, the impact of hepatic steatosis on liver metastasis is enigmatic. We find that while control mice were relatively resistant to hepatic metastasis, those which were lipodystrophic or obese, with NAFLD, had a dramatic increase in breast cancer and melanoma liver metastases. NAFLD promotes liver metastasis by reciprocal activation initiated by tumor-induced triglyceride lipolysis in juxtaposed hepatocyte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 37 publications
1
26
0
Order By: Relevance
“…NETosis is an important neutrophil function that can promote liver metastasis of breast cancer and different pro-metastatic neutrophil populations are highly metabolically adaptable, which facilitates the formation of liver metastases ( 145 ). The products of pathologically deposited lipids can promote metastasis and nonalcoholic fatty liver disease (NAFLD) activates tumor-induced triglyceride lipolysis in juxtaposed hepatocytes, thereby promoting breast-to-liver metastasis ( 146 ). In addition to genetic tendency, metastatic cells that inhabit the brain are adaptive to crosstalk with many different brain residential cells ( 112 , 147 ).…”
Section: Metabolic Reprogramming and Organ-specific Metastasismentioning
confidence: 99%
“…NETosis is an important neutrophil function that can promote liver metastasis of breast cancer and different pro-metastatic neutrophil populations are highly metabolically adaptable, which facilitates the formation of liver metastases ( 145 ). The products of pathologically deposited lipids can promote metastasis and nonalcoholic fatty liver disease (NAFLD) activates tumor-induced triglyceride lipolysis in juxtaposed hepatocytes, thereby promoting breast-to-liver metastasis ( 146 ). In addition to genetic tendency, metastatic cells that inhabit the brain are adaptive to crosstalk with many different brain residential cells ( 112 , 147 ).…”
Section: Metabolic Reprogramming and Organ-specific Metastasismentioning
confidence: 99%
“…In animal study, high fat diet-induced steatosis profoundly increase liver metastasis in a splenic injection model of experimental liver metastasis using syngeneic MC38 colon cancer cells ( 38 ). Referring to potential mechanisms that contribute to CRLM, Li et al ( 39 ) found that mice with hepatic steatosis have a marked predisposition to liver metastasis, which is unusual in non-steatotic mice. The mechanism is that lipolytic products are transferred to cancer cells via fatty acid transporter protein 1, and promote cancer cells growth by mitochondrial oxidation ( 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…Referring to potential mechanisms that contribute to CRLM, Li et al ( 39 ) found that mice with hepatic steatosis have a marked predisposition to liver metastasis, which is unusual in non-steatotic mice. The mechanism is that lipolytic products are transferred to cancer cells via fatty acid transporter protein 1, and promote cancer cells growth by mitochondrial oxidation ( 39 ). Hepatic steatosis can cause extracellular matrix (ECM) remodeling and reorganization, which create a fibrotic niche for CRLM and is important in tumor promotion and growth ( 40 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that glucose metabolism, particularly glycolysis, is of great significance in tumour development and metastasis 20 – 22 . Abnormal lipid metabolism is associated with the growth and metastatic cascade of HCC and other tumours 23 , 24 .…”
Section: Resultsmentioning
confidence: 99%